Copper Nanoparticles on Montmorillonite K-10: A Versatile Catalyst for the One-Pot Synthesis of 3,5-Disubstituted Isoxazoles Using Various Methodologies - Stabile, Santiago; Bjerg, Esteban E.; Radivoy, Gabriel (Synthesis, 2023)
A readily prepared and versatile heterogeneous catalyst composed of copper nanoparticles supported on montmorillonite K-10 (CuNPs/MK-10) has proven to be highly effective in catalyzing the synthesis of isoxazoles through various one-pot methodologies with high atom economy. These methodologies allow for the use of readily available starting materials, including aldehydes and alkynes through 1,3-dipolar cycloaddition reactions, as well as via cycloisomerization of ynones. Additionally, the CuNPs/MK-10 catalyst promoted the in situ formation of the ynones via an acyl Sonogashira coupling. Furthermore, a three-step one-pot methodology was also developed, starting from carboxylic acids and involving the in situ generation of acyl chlorides.
Keywords: isoxazole synthesis; copper nanoparticles; heterogeneous catalysis; 1,3-dipolar cycloaddition; cycloisomerization